Incorporation of a simplified mechanical joint model into numerical analysis - Glavan, Mitja (Strojniški vestnik, 2022)
In the development of new joining technologies, incorporation of mechanical joints in computer analyses for the evaluation of structures can be carried out by a practical, simplified mechanical joint model. Here, two most frequently used joining technologies were analysed, a self-piercing rivet joint and a clinch joint. Physical tests of static load capacity of the joints were performed and numerical models for simulations were set-up. An optimization method was designed for estimating the material parameters of the mechanical joint for the needs of numerical analyses. For optimization purposes during the plan of experiments, a range of possible parameter values was investigated using a response surface method, results of simulations, results of physical tests and a genetic algorithm. The results of simulations using the optimal values of the material parameters are comparable to the experimental observations for the both joints.
Keywords: clinch joints; genetic algorithm; mechanical joints; mehanski spoji; metoda končnih elementov; odzivna površina, genetski algoritem; optimizacija parametrov; parameter optimization; response surface; samorezno kovičenje; self-piercing riveting; simplified FE model; zagozdni spoji